Raees Warsi as Hymn Writer - Atia Sarfraz; Dr. Sadaf Naqvi (Zaban-o-Adab, 2024)
Raees Warsi is insightful intellectual and discerning person well known/famous poet of current age/era. His style of thinking and writing and research poetry, use of sweet and delicate/decent words and his tone and religious poetry/divine poetry are absolutely beautiful. As a poet of Naat-e-Rasool-e-Maqbool Raees, Warsi has not only focused his attention on Holy Prophet Muhammad’s (PBUH) commendation but also he tried to convey Holy Prophet, Hazrat Muhammad (PBUH) perpetual/eternal message in all over the world. His book “The Universe of Heart” encompasses Allah’s Hymn, Naat and splendid attributes of Hazrat Muhammad’s members of family (Ahlay Bait). He has made best efforts to describe/express Seerat-un-Nabi in shape of poetry/poetic verses and his eulogistic oration/poetry (Panegyric poetry) reflects refreshing and soothing tone. Remembering our beloved Holy Prophet, Hazrat Muhammad (PBUH) makes our lips more beautiful and sweet. Holy Prophet Source to be steadfast in believing One Allah. In his eulogistic oration in shape of Naat-e-Rasool-Maqbool is the representation of verses of the Holy Quran reflects teachings extracted/abstracted from the Holy Sunnah and Ahadith is very clear and bright.